Seasonality of pCO2 and air-sea CO2 fluxes in the Central Labrador Sea - Arruda, Ricardo; Atamanchuk, Dariia; Boteler, Claire; Wallace, Douglas W. R. (Frontiers in Marine Science, 2024)
The Labrador Sea in the subpolar North Atlantic is known for its large air-to-sea CO2 fluxes, which can be around 40% higher than in other regions of intense ocean uptake like the Eastern Pacific and within the Northwest Atlantic. This region is also a hot-spot for storage of anthropogenic CO2. Deep water is formed here, so that dissolved gas uptake by the surface ocean directly connects to deeper waters, helping to determine how much atmospheric CO2 may be sequestered (or released) by the deep ocean. Currently, the Central Labrador Sea acts as a year-round sink of atmospheric CO2, with intensification of uptake driven by biological production in spring and lasting through summer and fall. Observational estimates of air-sea CO2 fluxes in the region rely upon very limited, scattered data with a distinct lack of wintertime observations. Here, we compile surface ocean observations of pCO2 from moorings and underway measurements, including previously unreported data, between 2000 and 2020, to create a baseline seasonal climatology for the Central Labrador Sea. This is used as a reference to compare against other observational-based and statistical estimates of regional surface pCO2 and air-sea fluxes from a collection of global products. The comparison reveals systematic differences in the representation of the seasonal cycle of pCO2 and uncertainties in the magnitude of air-sea CO2 fluxes. The analysis reveals the paramount importance of long-term, seasonally-resolved data coverage in this region in order to accurately quantify the size of the present ocean sink for atmospheric CO2 and its sensitivity to climate perturbations.